Some aspects of the Italian demographic situation: the first results of the 1951 census - N. FEDERICI (PSL Quarterly Review, 2014)
The article analyses the census of population and of dwellings carried out in Italy in November, 1951, throwing light on demographic trends in comparison with those of other populations of white race, i.e. on Italy’s present position of transition from an intermediate stage to one of a rapidly ageing population. The writer also calls attention to the uneven development of the population as between the various areas and regions of Italy, underlying among other matters the growing degree of urban concentration. The last paragraphs, setting forth the results of the census returns on dwellings, hep to bring once more to the fore the problem of housing, which is still a serious one in Italy in spite of the reconstruction and new building carried out since the war.